Heart transplantation for end-stage heart failure combined with Q fever isolated to the heart: a case report. Issue 6 (5th December 2020) - van 't Veer, Marcel; Otterspoor, Luuk; de Regt, Marieke; Peels, Kathinka; evens, Jola; Vink, Aryan; de Jonge, Nicolaas
Abstract: Background : Active infection is generally considered a contraindication for heart transplantation. The rare combination of a patient with an active Coxiella burnetii infection and a congenital corrected transposition of the great arteries requiring heart transplantation impose challenging treatment decisions. We would like to demonstrate that if Q fever is restricted to the heart only, heart transplantation is also beneficial from an infectious point of view, therefore treating two severe conditions simultaneously. Case summary : A patient with end-stage heart failure due to congenital corrected transposition of the great arteries and requiring heart transplantation developed chronic Q fever and endocarditis. Different antibiotic regimes were tried due to severe adverse reactions. Antibiotic treatment was precisely monitored by measuring Q fever polymerase chain reaction (PCRs) and phase I IgG antibody titres. A positron emission tomography scan revealed that Q fever was confined to the heart only after which it was decided to perform heart transplantation. Based on the results of PCR and antibody testing, antibiotic treatment was stopped after 1 year. After 5 years of follow-up, patient is still in an optimal condition. Discussion : In case of a patient with end-stage heart failure and chronic Q fever, a combined treatment with PCR-/antibody monitored antibiotics and heart transplantation can cure both conditions.